Profile of Students' Critical Thinking Skills and Digital Literacy in Energy Sources Material - Suminarsih Suminarsih; Nur Khoiri; Harto Nuroso (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
Critical thinking skills help students analyse information deeply, make rational decisions, and solve problems creatively. Meanwhile, digital literacy is a key competency for navigating the rapid, diverse flow of information in today’s technological era. The purpose of this study is to examine students’ profiles of critical thinking skills and digital literacy in physics learning. This research employs a descriptive qualitative design. Data on critical thinking skills were collected through written tests containing descriptive questions. Students' digital literacy skills were measured using a questionnaire on student learning habits with digital media. The results of this study indicate that, in general, students' critical thinking skills in physics learning are currently in the category, with an average percentage of 68,4% however, students' weaknesses are visible in the indicators, conclude and set strategy and tactics, each with a percentage 62% and 56%, which is in the category low. Skill analysis results: digital literacy students showed better achievement, with an average percentage of 68,2%, which is in the good category. However, as with critical thinking skills, challenges arise in indicators' digital content production (58%) and personal data security (63%), both of which are in the 'enough' category. These results indicate that although students already possess basic critical thinking and digital literacy skills, several important aspects need improvement. This improvement can be achieved through a more integrated physics learning, with activities that emphasise in-depth analysis, information synthesis, and the safe and secure production of digital content.